Molecular study of the status of Angiostrongylus cantonensis in rats in Haiti. - Fedna, Jimmy; Borne, Romain; Rieffel, Dominique; Bornette, Gudrun; Henrys, Jean-Hugues; Grenouillet, Frédéric; Raoul, Francis (Parasite, 2024)
Angiostrongylus cantonensis, commonly known as the rat lungworm, causes Eosinophilic meningitis in humans. Our study aimed to investigate the prevalence and distribution of this parasite in rats in Haiti. Rats were trapped at 8 sites, 7 in Artibonite (rural region) and one in an urban area of Port-au-Prince. After euthanasia, hearts and lungs were sampled and preserved in 70% ethanol. Subsequently, the organs were dissected to detect adult worms. Parasite DNA was amplified using PCR targeting either the nematode ITS2 gene for rodent lung tissue or cox1 for isolated worms. Subsequent sequencing allowed parasite identification. A total of 70 rats were captured, i.e. 23 Rattus norvegicus and 47 Rattus rattus. Adult nematodes morphologically compatible with A. cantonensis were isolated from 5/70 rats (7%) and identification was confirmed by sequencing. Molecular analysis of lung tissue revealed a parasite prevalence of 31.4% (22/70), and its presence at 4 of the 8 sites investigated, including Port-au-Prince. The molecular approach on lung tissue targeting the ITS2 gene enabled us to detect a prevalence 4 times higher than the visual search for adult worms alone. Only one COX1 haplotype was identified, belonging to genotype II-G, widely distributed in Brazil, the French Antilles (Guadeloupe), French Polynesia, Hawaii, and Japan. These results confirm that A. cantonensis is an endemic parasite in Haiti not only in the capital Port-au-Prince, but also in several rural areas. Direct molecular screening for Angiostrongylus DNA in rat lung tissue showed higher sensitivity than visual detection of worms during dissection and could be useful for further prevalence studies.